Genomic Prediction Strategies for Dry-Down-Related Traits in Maize - Ni, Pengzun; Anche, Mahlet Teka; Ruan, Yanye; Dang, Dongdong; Morales, Nicolas; Li, Lingyue; Liu, Meiling; Wang, Shu; Robbins, Kelly R. (Frontiers in Plant Science, 2022)
For efficient mechanical harvesting, low grain moisture content at harvest time is essential. Dry-down rate (DR), which refers to the reduction in grain moisture content after the plants enter physiological maturity, is one of the main factors affecting the amount of moisture in the kernels. Dry-down rate is estimated using kernel moisture content at physiological maturity and at harvest time; however, measuring kernel water content at physiological maturity, which is sometimes referred as kernel water content at black layer formation (BWC), is time consuming and resource demanding. Therefore, inferring BWC from other correlated and easier to measure traits could improve the efficiency of breeding efforts for dry down related traits. In this study, multi-trait genomic prediction models were used to estimate genetic correlations between BWC and water content at harvest time (HWC) and flowering time (FT). Results show there is moderate to high genetic correlation between the traits (0.24 to 0.66), which supports the use of multi-trait genomic prediction models. To investigate genomic prediction strategies, several cross-validation scenarios representing possible implementations of genomic prediction were evaluated. Results indicate that, in most scenarios, the use of multi-trait genomic prediction models substantially increase prediction accuracy. Furthermore, the inclusion of historical records for correlated traits can improve prediction accuracy, even when the target trait is not measured on all the plots in the training set.